THE INEXTRICABLE LINKS OF THE DIGITAL ECONOMY AND THE FINANCIAL SYSTEM AND MODERN INFORMATION TECHNOLOGIES (American Journal of Interdisciplinary Research and Development, 2022)
The article discusses the key directions and nature of the development of financial systems influenced by the digital economy and society. An analysis of the individual components of the financial system has been carried out and the nature of digitization in each of them has been identified. As a result, four key trends in the development of the financial system driven by the digital economy have been highlighted. The first trend: strengthening the role of remote interaction between financial institutions and end-users of financial products and services. The second trend: redistribution of the financial services market manifested in enhanced horizontal integration of financial institutions. The third trend: changing consumer behavior, requiring a review of existing business processes and regulations, and the development of the technological basis of the financial system. The fourth trend: the blurring of distinctions between the financial system and other sectors of the economy manifested in the partial substitution of traditional finance companies by high-tech companies. Digitization has been shown to have a definite positive impact on the financial system, making it more efficient, accessible, flexible and transparent. However, working with the digital financial system requires the user to have appropriate digital and financial competencies. This gives rise to the problem of managing the awareness-building of population and providing assistance to the most disadvantaged groups.